Rooted in Place: The Distinctive Ecology of Rural Social Innovation and Its Implications for Inclusive Development Policy in Indonesia - Dhanny Septimawan Sutopo; Arief Budi Nugroho (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Rural social innovation has emerged as a critical yet undertheorised domain within the broader social innovation literature. While existing scholarship tends to treat social innovation as a universal phenomenon, this article argues that rural contexts produce a structurally distinct form of innovation — one governed by place-embeddedness, communal ownership, resource ingenuity, and indigenous epistemic traditions. Drawing on the Indonesian case, where over 74,961 villages serve as laboratories of grassroots change, this article develops the PLACE Model (Place-embeddedness, Local agency, Adaptive capacity, Communal reciprocity, and Epistemic plurality) as a conceptual framework for understanding rural social innovation on its own terms. The article further analyses empirical data from village-level programs — including BUMDes (Village-Owned Enterprises), Desa Digital initiatives, and community health cooperatives — to demonstrate how rural innovations depart from dominant, market-centric models of innovation. The findings have significant implications for policy design, scholarly theorisation, and development practice in the Global South. Keywords: rural social innovation, place-based development, PLACE Model, BUMDes, Indonesia, inclusive development, community-driven development